ON SYMMETRIC BI-DERIVATIONS OF KU-ALGEBRAS - YILDIRIM, OMER; Ayar Özbal, Sule (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
The notion of left-right (resp. right-left) symmetric biderivation of KU-algebras is introduced and some related properties are investigated.